Makna Pendidikan dalam Perspektif Islam dan Relevansinya dengan Pendidikan di Indonesia - Reza Alinata; Winda Atika Sari; Yuli Kartika Putri (STIKes Ibnu Sina Ajibarang, 2024)
The first revelation in Q.S. al-'Alaq: 1-5 in rejecting ignorance, injustice, and monopoly, and emphasizing education to form intelligent individuals and Qur'anic characters. The verse inspires the formation of a progressive and civilized society. Ideal education should not only rely on empirical theories but should also integrate essential metaphysical concepts. In Arabic, educational terms such as ta'lim, tadris, and ta'dib have different but complementary meanings, highlighting aspects of teaching, formal instruction, and moral education. Islamic education combines scientific knowledge with spiritual values, forming individuals with morals and integrity. The thoughts of Ki Hajar Dewantara and K.H. Ahmad Dahlan were instrumental in shaping Indonesian national education, emphasizing character, religiosity, and modern knowledge. This integrative effort reflects an education that is inclusive, equitable, and encourages students' creativity and independence to face global challenges.